Trust and Distrust in Carbon Capture and Utilization Industry as Relevant Factors for the Acceptance of Carbon-Based Products - Offermann-van Heek, Julia; Arning, Katrin; Linzenich, Anika; Ziefle, Martina (Frontiers in Energy Research, 2018)
Climate change poses a key threat to today's societies and is caused by greenhouse gas emissions, mainly carbon dioxide emissions. Capture and Utilization of Carbon Dioxide (CCU) is a technological approach to reduce CO2 emissions. Coincidentally, the approach also reduces the depletion of limited fossil resources by incorporating CO2 as a raw material in the manufacture of products (e.g., plastics), thereby replacing fossil resources such as conventionally used oil. Even though some CCU products are nearing market maturity, systematic research on the acceptance of these products, especially regarding the (dis)trust in the companies that produce them, is still in its initial phase. Since a lack of trust could lead to a rejection of innovative products and technologies, the present study empirically investigates (dis)trust factors related to the acceptance of CCU plastic products. In a first step, interviews were carried out and analyzed to reveal relevant (dis)trust criteria for credibility of companies, desired information and marketing issues, and how CCU products are perceived. Afterwards, an online survey (n = 127) was conducted to identify and quantify important (dis)trust dimensions, and their connection to the acceptance of CCU products. The results showed that the participants had a slightly positive attitude toward CCU, and potential environmental, sustainability related, and economic benefits were acknowledged. In addition, potential barriers of CCU (sustainability risks, unknown risks, and health concerns) were rated rather neutrally and were thus not perceived as real barriers of CCU. When comparing companies to other institutions (e.g., research institutions, NGOs), the participants reported to trust companies least. Furthermore, four relevant trust (e.g., customer relationship) and distrust (e.g., bad customer orientation) dimensions were identified using CCU companies as an example of companies which manufacture innovative products. Finally, some first insights concerning the connection between the identified trust factors, CCU perception, credibility of the information sources, and the marketing of innovative products, are presented. The results enable deriving user-specific CCU product communication and information strategies.